KO-GASIFIKASI CAMPURAN TONGKOL JAGUNG DAN TEMPURUNG KELAPA MENGGUNAKAN DOWNDRAFT GASIFIER - , EKO FAJAR NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gasification of waste corn cob is one of the technologies to convert solid waste into energy corn cobs in the form of gas using a gasifier. Results of previous research showed that the conversion process using a downdraft gasifier, waste corn cob has a disadvantage that the process of gasification is not stable because of the low density. By mixing other biomass such as coconut shell which has a higher density value is expected to overcome these problems. This study was conducted to determine the combination of the optimum mix between corn cobs and coconut shell that produces the best performance in the gasification process using type of downdraft gasifier. The research carried out by adding a mixture of coconut shell at 0%, 5%, 10%, 15%, and 20%. Parameters measured were temperature of reduction zone and the stove temperature, the volume of tar, the mass of residual gasification, effective flame time, operating time, and frequency of compaction. The results showed that the variation of the mixture influences on the stove temperature, operating time, effective flame time, mass of residual gasification and frequency of compaction but no effect to the reduction zone temperature and the volume of tar. The addition of coconut mixture on the percentage of corn cobs raise the performance of stove temperature linierly, extend the effective flame in the amount of 8-15 minutes, and decrease the frequency of compaction during the gasification process. The best mixture of coconut shell based on a combination of several performance parameters that are measured on a mixture of 15%.